1987
DOI: 10.1021/jo00388a033
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective cycloadditions of N-protonated azomethine ylides and 2-azaallyl anions generated from N-(silylmethyl) thioimidates, synthetic equivalents of nonstabilized nitrile ylides

Abstract: Trimethylsilylmethyl isothiocyanate (I) reacts consecutively with the Grignard compounds (II) and the halides (III) to form the thioimidates (IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The selectivity of this side reaction can be explained by the fact that anti-4 adopts an extended conformation (Figure 1), whereas in the syn-diastereomer, the repulsion between the band the Whereas the non-destructive deprotonation of a-aminonitriles with free NH protons requires the presence of a stabilizing a-substituent such as an aromatic, heteroaromatic or olefinic group in order to prevent a retro-Strecker reaction, 22 a-(alkylideneamino)nitriles 5 are much more CHacidic and can be easily deprotonated even if no stabilizing a-substituent is present. [23][24][25] We tested several conditions for the addition reaction and found that either phasetransfer conditions (7.9 M KOH/CH 2 Cl 2 , 10 mol% BnNEt 3 Cl) 26,27 or the use of metal-free bases such a DBU or Me 4 NOH furnishes the desired products. In most cases, the biphasic system gives somewhat higher yields although side reactions may occur.…”
Section: Methodsmentioning
confidence: 99%
“…The selectivity of this side reaction can be explained by the fact that anti-4 adopts an extended conformation (Figure 1), whereas in the syn-diastereomer, the repulsion between the band the Whereas the non-destructive deprotonation of a-aminonitriles with free NH protons requires the presence of a stabilizing a-substituent such as an aromatic, heteroaromatic or olefinic group in order to prevent a retro-Strecker reaction, 22 a-(alkylideneamino)nitriles 5 are much more CHacidic and can be easily deprotonated even if no stabilizing a-substituent is present. [23][24][25] We tested several conditions for the addition reaction and found that either phasetransfer conditions (7.9 M KOH/CH 2 Cl 2 , 10 mol% BnNEt 3 Cl) 26,27 or the use of metal-free bases such a DBU or Me 4 NOH furnishes the desired products. In most cases, the biphasic system gives somewhat higher yields although side reactions may occur.…”
Section: Methodsmentioning
confidence: 99%
“…9 Again, the intermediate is a less-stabilized 2-azaallyl anion, i.e., 24, although some stabilization by the sulfur substituent may be involved. However In 1987, the same group reported the desilylation of thioimidates such as 23 in the presence of electron-poor alkenes to afford pyrrolines such as 25 (Scheme 7).…”
Section: Nonstabilized 2-azaallyl Anionsmentioning
confidence: 99%
“…9 We have found it possible to generate 2-azaallyllithiums bearing heteroatoms such as oxygen, sulfur, and nitrogen by tin-lithium exchange on imidates, thioimidates, and amidines such as 93-95 (Scheme 22). 9,11 Only Tsuge, Kanemasa, and co-workers have reported nonstabilized 2azaallyl anions bearing a heteroatom (sulfur), although their cycloadditions appear to be limited to electron-poor alkenes (see Scheme 7 above).…”
Section: Heteroatom-substituted 2-azaallyllithiumsmentioning
confidence: 99%
“…In 1987, the same group reported the desilylation of thioimidates such as 23 in the presence of electron-poor alkenes to afford pyrrolines such as 25 (Scheme 7). 9 Again, the intermediate is a less-stabilized 2-azaallyl anion, i.e., 24, although some stabilization by the sulfur substituent may be involved. Only electron-deficient alkenes were reported to undergo cycloadditions with these anions.…”
Section: Nonstabilized 2-azaallyl Anionsmentioning
confidence: 99%